Preterm Singleton Birth Rate during the COVID-19 Lockdown: A Population-Based Study - Leibovitch, Leah; Reichman, Brian; Mimouni, Francis; Zaslavsky-Paltiel, Inna; Lerner-Geva, Liat; Wasserteil, Netanel; Sagiv, Nadav; Daas, Suha; Almashanu, Shlomo; Strauss, Tzipora (American Journal of Perinatology, 2021)
Objective The aim of the study is to evaluate the effect of the coronavirus disease 2019 (COVID-19) pandemic national lockdown period on the rate of singleton preterm births in Israel.Study Design This is a population-based cohort study of 3,41,291 singleton infants born in the months of January to July 2017 to 2020. Multivariable logistic regression analyses were used to estimate the influence of period and year on the rates of preterm births during the lockdown period (11th March − 5th May 2020) compared with rates before (January 1st 2020 − March 10th 2020), and after the lockdown (May 6th 2020–June 30th 2020) and to the corresponding periods in 2017to 2019.Results During the lockdown period the preterm birth rate (primary outcome) decreased by 9.7% from 5.05 to 4.56% in the pre-lockdown period (p = 0.006), an adjusted decrease of −0.52% (95% confidence interval −0.89%; −0.15%), odds ratio 0.898 (95% confidence interval 0.832; 0.970).Conclusion The rate of singleton preterm births declined by 9.7% during the COVID-19 pandemic national lockdown period in Israel.Key Points
Keywords: COVID-19; prematurity; lockdown